Chaos Theory: Implications for Supply Chain Management. - Wilding, Richard D. (MCB, 1998)
Since the late 1950's it has been recognized that the systems used internally within supply chains can lead to oscillations in demand and inventory as orders pass through the system. The uncertainty generated can result in late deliveries, order cancellations and an increased reliance on inventory to buffer these effects. Despite the best efforts of organizations to stabilize the dynamics generated, industry still experiences a high degree of uncertainty. The failure to significantly reduce uncertainty through traditional approaches may in part be explained by chaos theory. This paper defines deterministic chaos and demonstrates that supply chains can display some of the key characteristics of chaotic systems, namely: chaos exhibits sensitivity to initial conditions; it has Islands of Stability; generates patterns; invalidates the reductionist view; and, undermines computer accuracy. The implications for the management and design of supply chains are discussed.
Keywords: Chaos; Costs; Supply-chain management; Warehousing